Early Detection of Fragile X Syndrome: Applications of a Novel Approach for Improved Quantitative Methylation Analysis in Venous Blood and Newborn Blood Spots. (1st July 2014) - Inaba, Yoshimi; Schwartz, Charles E; Bui, Quang M; Li, Xin; Skinner, Cindy; Field, Michael; Wotton, Tiffany; Hagerman, Randi J; Francis, David; Amor, David J; Hopper, John L; Loesch, Danuta Z; et al.
Abstract: BACKGROUND: Standard fragile X syndrome (FXS) diagnostic tests that target methylation of the fragile X mental retardation 1 ( FMR1 ) CpG island 5′ of the CGG expansion can be used to predict severity of the disease in males from birth, but not in females. METHODS: We describe methylation specific–quantitative melt analysis (MS-QMA) that targets 10 CpG sites, with 9 within FMR1 intron 1, to screen for FXS from birth in both sexes. The novel method combines the qualitative strengths of high-resolution melt and the high-throughput, quantitative real-time PCR standard curve to provide accurate quantification of DNA methylation in a single assay. Its performance was assessed in 312 control (CGG <40), 143 premutation (PM) (CGG 56–170), 197 full mutation (FM) (CGG 200–2000), and 33 CGG size and methylation mosaic samples. RESULTS: In male and female newborn blood spots, MS-QMA differentiated FM from control alleles, with sensitivity, specificity, and positive and negative predictive values between 92% and 100%. In venous blood of FM females between 6 and 35 years of age, MS-QMA correlated most strongly with verbal IQ impairment ( P = 0.002). In the larger cohort of males and females, MS-QMA correlated with reference methods Southern blot and MALDI-TOF mass spectrometry ( P < 0.05), but was not significantly correlated with age. Unmethylated alleles in high-functioning FM and PM males determined by both reference methods were also unmethylated by MS-QMA. CONCLUSIONS: MS-QMA has an immediate application in FXS diagnostics, with a potential use of its quantitative methylation output for prognosis in both sexes.